'Children of the Prophets and the Covenant': A Post-Supersessionist Reading of Luke-Acts - Moraff, Jason F. (Religions, 2023)
Luke-Acts is a theocentric narrative. It tells how God in and through Jesus acts out of faithfulness to the covenant on behalf of Israel. This article uses this fundamental claim to offer a post-supersessionist reading of Luke-Acts. It contends that genealogical Israel (the Jewish people) remains God’s people because of election. God turns to Israel offering forgiveness and salvation. The people struggle to respond. All Israel, including Jesus’s disciples, stumbles. Some Jewish people are more faithful, others less. Together they comprise the less-than-faithful people of God to whom God is faithful. Luke’s Jesus and Paul embody this dynamic. Jesus recapitulates Israel’s history, acting faithfully on its behalf for its salvation. He dies in solidarity with the Jewish people, faithful and unfaithful alike. He is raised, proleptically guaranteeing their restoration. Paul embodies how God remains loyal to recalcitrant Israel. Apart from repentance from Paul, an encounter with the risen Lord transforms this “God-fighter” simply because he is a “chosen vessel”. In Paul, Luke narrates God’s radical fidelity to Israel. God will restore Israel, opening blind eyes to see Jesus as messiah. The article distills the author’s forthcoming monograph Reading Luke-Acts after Supersessionism: The Salvation of Israel and the Nations in Accordance with the Scriptures.